Perancangan Sistem Filtrasi Air Berbasis Virtual Programmable Logic Controller (PLC) dan Human-Machine Interface (HMI) - Bachri, Karel Octavianus; Karangga, Yusaphat Phosa; Mahyastuty, Veronica Windha; Sereati, Catherine Olivia; Mulyadi, Melisa; Octaviani, Sandra (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2024)
In the industrial environment, automation technology is becoming increasingly vital for boosting process efficiency and dependability. Water filtration is one of the most essential industrial uses. This study aims to evaluate the performance of PLC virtual control systems in regulating and managing water filtration processes, and HMI provides an intuitive graphical interface for operators to monitor and control processes. The simulation in this study employs the integrated Virtual PLC Codesys Virtual Win V3 and HMI Aveva Intouch software. Turbidity sensors are used to confirm the clarity of water after it has been filtered. The results of this study demonstrate that using the virtual control system, PLC and HMI, can facilitate the operation and monitoring of water filtration.